THE INFLUENCE OF APPLICATION OF COMPENSATION SYSTEM ON EMPLOYEE TURNOVER INTENTION AT PT.AUTO PADU KUALA TANJUNG BATUBARA WITH WORK MOTIVATION AS AN INTERVENING VARIABLE - Rico Nur Ilham; Lala Merlita; Muhammad Multazam; T.M Azani; Ikram (Universitas Efarina, 2023)
In this study the population is permanent employees of PT. Auto Padu Kuala Tanjung Batu Bara, namely as many as 30 people. Because the target population is less than 100, the sampling technique used is the census method, where the entire population is 30 permanent employees of PT. Auto Padu Kuala Tanjung Batu Bara which will be used as a research sample. the first hypothesis is accepted, meaning that compensation (X) has a positive and significant effect on work motivation (Z). the second hypothesis is accepted, meaning that compensation (X) has a positive and significant effect on Turnover Intention (Y). the third hypothesis is rejected, meaning that Work Motivation (Z) has no positive and significant effect on Turnover Intention (Y).